The Recovery Rate of New Thallus LAJU RECOVERY THALLUS BARU PADA RUMPUT LAUT Kappaphycus alvarezii YANG TERPOTONG BEKAS GIGITAN IKAN DI PERAIRAN PANTAI BONE BONE - Musdalifa AP AP (Universitas Mataram, 2024)
Thallus when eaten by fish will be physically damaged or cut off due to fish bites. Seaweed has the ability to recover from damage. For this reason, research will be conducted on the extent to which seaweed will carry out the recovery rate due to damage to the thallus that is cut off by fish-eaten bites. This study aims to determine the rate of thallus recovery due to being eaten by fish using the Horizontal Net method in the waters of Bone Bone Beach. Seaweed was put into the horizontal net with herbivorous fish (baronang). One week later the thallus was weighed at an initial weight of 50g. For observation of recovery used digital camera microscope magnification 1000x every 2 days sampling. For the growth rate of seaweed samples were weighed using analytical scales every 7 days. Water quality measurements during the study included salinity, temperature, brightness, current velocity, pH, nitrate and phosphate. The growth rate obtained is classified as good but has not reached the best level, a good growth rate is not less than 3%. The recovery rate maintained in the recovery horinet for 20 days during the maintenance period and the emergence of new thallus returns at the age of 15-20 days during maintenance. The results of the correlation between LPS and recovery rates with environmental factors show a strong correlation relationship so that environmental factors affect the rate of recovery of new thallus Kappaphycus alvarezii.